The In-Hospital Cost of Ventricular Assist Device Therapy: Implications for Patient Selection. Issue 6 (November 2017) - Iyengar, Amit; Kwon, Oh Jin; Tamrat, Msgana; Salimbangon, Anthony; Satou, Nancy; Benharash, Peyman; Ardehali, Abbas; Shemin, Richard J.; Kwon, Murray H.
Abstract : Ventricular assist device (VAD) therapy is increasingly utilized to support patients in end-stage heart failure. However, VAD programs are resource intensive and demand active monitoring to ensure long-term sustainability. The purpose of this study was to analyze total cost trends of the VAD program at our academic medical center. Retrospective analysis of University of California - Los Angeles's VAD program between 2013 and 2014 was performed. Total in-hospital costs from the date of VAD surgery admission were queried and normalized to a z score. Multivariable linear regression analysis with step-wise elimination was used to model total costs. Overall, 42 patients received a VAD during the study period, with 19 (45%) receiving biventricular support. On univariate analysis, high body mass index, biventricular support, time between VAD implantation and discharge, and total length of hospital stay were correlated with higher costs (all p < 0.02). On multivariable analysis, time between VAD implantation and discharge and biventricular support remained significantly related to total costs (overall R 2 = 0.831, p < 0.001). The time between VAD implantation and discharge and the use of biventricular support were the most predictive factors of total cost in our VAD population. Reducing hospital stay post-VAD implantation is important in minimizing the cost of VAD care.